Factor analysis of socio-economic determinants of diseases - Khanum, Shakila; Ansari, Bilal Anjum; Hussain, Anila; Qasim, Huma (International Journal of Scientific World, 2016)
Our each and every part of life is persuaded by diversity of factors. Social and economic factors have a huge impact on person’s health. The purpose of this study is to investigate the social and economic determinants of diseases by a statistical technique called factor analysis using SPSS version 21. Sample of 1500 male and female patients from public and private hospitals of Southern Punjab, Pakistan is utilized using saturation sampling technique. Results illustrate that gender, age, area living, migration of ancestors, gender of house hold head, respondent’s and parent’s educational level, marital status, family size and monthly income are the major social and economic determinants of diseases. Age is the major factor that affects a person’s health. As age increase the chances of getting affected by disease also increase. So we can say that age and probability of getting ill are directly proportional to each other. Same is the case with income and education. Males are found to get ill more often, relatively compared to females.